Biomechanical Evaluation of the Transcortical and Transpedicular Trajectories for Pedicle Screw Insertion in Thoracolumbar Fracture Fixation for Ankylosing Spondylitis - Tong, Zhizhong; Xiao, Bin; Yan, Kai; Xing, Yonggang; Zhang, Yanbin (Frontiers in Surgery, 2021)
Background: Ankylosing spondylitis (AS) is a chronic disorder characterized by an imbalance between bone formation and resorption. Spinal fractures often occur after minor trauma in patients with AS. For thoracolumbar fractures, transpedicular screw (TPS) fixation through the posterior approach has been suggested. The cortical bone trajectory (CBT) technique has also been used to prevent screw pull-out in patients with poor bone quality. The aim of current study was to assess the biomechanical characteristics of the TPS and CBT technique in thoracolumbar AS fracture fixation by finite element analysis. Methods: The three-dimensional finite element models of the AS spine were created. The CBT and TPS methods of screw insertion were used in AS spinal fracture models. An intact AS spine model was considered the control. An axial force and torsion in rotation, flexion/extension and lateral flexion were applied in all models in CBT, TPS, and control groups. Results: Both the CBT and TPS techniques were unable to restore the construct stiffness of the fractured AS spine under axial, rotational, and flexion/extension loading. The TPS technique showed better intact stability under all loading conditions. Similarly, the TPS technique provided superior fracture regional stability against axial and rotational loads than did the CBT technique. The maximum von Mises stresses were 1714.4±129.8 MPa and 1208.7± 107.3 MPa (p<0.001), which occurred in the CBT and TPS groups under compressive loading. Conclusions: The TPS technique provides better biomechanical strength under axial, rotational, flexion/extension, and lateral flexion loading than does the CBT technique. Compared with CBT, TPS is more effective in maintaining the stability of AS thoracolumbar fractures from a finite element analysis perspective.